2021
DOI: 10.1108/mbe-02-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability for competitiveness in firms – a systematic literature review

Abstract: Purpose This paper aims to present a systematic review of the literature on sustainability for the competitiveness of firms to identify the state of the art, significant discussions and new research directions. Recently, due to the negative impacts that traditional and unsustainable practices of companies have caused the Planet (e.g. climate change, sanitary crisis), national and international research urgently calls for the assessment of sustainable practices in firms. However, progress seems slow due to a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 52 publications
0
9
0
2
Order By: Relevance
“…Considering recent meta analyses pertaining to Corporate Social Responsibility (CSR) and Sustainability in general, and to the SDGs in particular, we note that only very few recently published meta‐analysis articles have tackled the SDGs substantively whether in the title, abstract or content. These include an article by Lopez‐Torres et al (2021) on “Stakeholder Engagement, CSR Development and SDGs Compliance: A Systematic Review from 2015 to 2021,” which synthesizes the main approaches, issues and methodologies that have dominated in this field for the past 5 years, identifying trends and promising lines of scholarship pertaining to the relationships of Stakeholders, CSR, and Human Resources Management. Another relevant meta‐analysis review is presented by Park et al (2022), entitled “The Grand Challenge of Human Health: A Review and an Urgent Call for Business‐Health Research.” Here, the authors analyze the business‐health literature in the context of the ascendancy of SDG 3 on Good Health and Well‐Being.…”
Section: The Role Of Scholarship On the Sdgs: More Pressing Than Evermentioning
confidence: 99%
See 1 more Smart Citation
“…Considering recent meta analyses pertaining to Corporate Social Responsibility (CSR) and Sustainability in general, and to the SDGs in particular, we note that only very few recently published meta‐analysis articles have tackled the SDGs substantively whether in the title, abstract or content. These include an article by Lopez‐Torres et al (2021) on “Stakeholder Engagement, CSR Development and SDGs Compliance: A Systematic Review from 2015 to 2021,” which synthesizes the main approaches, issues and methodologies that have dominated in this field for the past 5 years, identifying trends and promising lines of scholarship pertaining to the relationships of Stakeholders, CSR, and Human Resources Management. Another relevant meta‐analysis review is presented by Park et al (2022), entitled “The Grand Challenge of Human Health: A Review and an Urgent Call for Business‐Health Research.” Here, the authors analyze the business‐health literature in the context of the ascendancy of SDG 3 on Good Health and Well‐Being.…”
Section: The Role Of Scholarship On the Sdgs: More Pressing Than Evermentioning
confidence: 99%
“…More broadly, there is a large set of review articles addressing different aspects of Sustainability but not touching on the SDGs specifically (e.g. Rathner, 2013, on Socially Responsible versus Conventional Investment Funds; Khizar et al, 2022, on the Conceptualization and Measurement Challenges of Sustainability Orientation; Lopez‐Torres et al, 2021, on Sustainability for Competitiveness for Firms; Carter & Easton, 2011, on Sustainable Supply Chain Management: Evolution and Future Directions; Khizar et al, 2021, on Business Orientation and Sustainable Development; Katz et al, 2022, on Employee Green Behavior: A Meta Analysis; Vysochan et al, 2021, on Sustainability Accounting; and Adhikariparajuli et al, 2021, on CSR Implications and Disclosure in Higher Education). These are just examples of relevant meta‐analysis reviews pertaining to Sustainability in general, highlighting some important angles being tackled in recent scholarship.…”
Section: The Role Of Scholarship On the Sdgs: More Pressing Than Evermentioning
confidence: 99%
“…Many firms have started putting more emphasis on greening their businesses and implementing sustainable operations in recent years (Katiyar et al, 2018;Lopez-Torres et al, 2021;Sahu et al, 2018a, b, c). The reason behind this emanates from external and internal forces that companies regularly face (Liu et al, 2021).…”
Section: Sustainability Processmentioning
confidence: 99%
“…In this sense, Gonzalez and Sanchez (2017) state that the capacity of companies to be competitive in the face of changing scenarios requires being part of the necessary responses to structure a sustainable company. enterprises (SMEs) (Bentivoglio et al, 2020;De Menezes et al, 2011;Lopez-Torres et al, 2021;Rajnoha et al, 2019). Furthermore, the research focused on a quantitative approach that measures the relationship between sustainability and competitiveness in SMEs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has reported organizational factors influencing sustainability at the firm level, such as organizational readiness and innovation, sustainability-oriented technology, the view and commitment to sustainability, more in the context of small and medium enterprises (SMEs) (Bentivoglio et al , 2020; De Menezes et al , 2011; Lopez-Torres et al , 2021; Rajnoha et al , 2019). Furthermore, the research focused on a quantitative approach that measures the relationship between sustainability and competitiveness in SMEs.…”
Section: Introductionmentioning
confidence: 99%